REGIONAL PECULIARITIES OF SCHOOL CHILDREN NUTRITION IN THE VORONEZH REGION - E. N. Myasnikova; T. V. Zhubreva; I. V. Vasilieva (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
High-quality nourishment of school children is an important factor of ensuring health and wellbeing of nation. The article gives information about providing hot meals to school children of comprehensive secondary institutions in the Voronezh region, which is one of the biggest entities of the Russian Federation. The region has its own specific features, typical illnesses included. For instance, school children in the region have a higher rate of illnesses of the digestion system, metabolism disorders, including overweight, some school children are registered in the TB prophylactic centers. The regional administration pays serious attention to organization of catering in education institutions. It was shown that provision of hot meals to school children in the region makes 92.7% on the average, while in 10 out of 31 municipal districts this figure reaches 100%. The governor’s program is functioning in the region, according to which school children from the 1 to the 10 form are provided with milk. The diet of school children includes iodized salt, bakery enriched with iodine-casein, vitamin drinks. However, school children have no opportunity to get complex prophylactic and medical nutrition, which corresponds to regional peculiarities on illnesses. In general, organization of school children catering is done in accordance with the current legislative regulations on the basis of state policy of the Russian Federation and its entities.